Pictorial Review of Paediatric Limp - Shashank Chapala; Sahana Giliyaru; Rajesh Botchu; Suvinay Saxena; Karthikeyan P. Iyengar; Muthusamy Chandramohan (Pediatric Reports)
A limp is an abnormal, uneven or laboured gait typically resulting from pain, weakness, or structural deformity involving the hip, lower limb, spine or abdominopelvic abnormalities. Limps in children are common and have diverse causes that can be benign to life-threatening including trauma, congenital malformations, and neoplastic diseases. Diagnosis involves identifying gait abnormality thoroughly examining history and physical exam, assessing tenderness and range of motion, and completing targeted lab and radiographic studies. We present an imaging review of various usual and unusual causes of limp in different age groups such as in toddlers (1–3 years), children (4–10 years), and adolescents (11–16 years) with a comprehensive literature review.